Pengaruh Pemberian Hukuman Dan Hadiah Terhadap Hasil Belajar Siswa SMP Negeri 9 Banjarmasin - Syahrijal, Syahrijal; Wati, Mustika (Berkala Ilmiah Pendidikan Fisika, 2015)
Empirically, be mentioned that punishment and reward giving effect on the motivation of student learning. Motivation that increasing will effect on result of student learning is still low. Therefore, researcher interested in doing this research with the goal to reveal the effect of reward and punishment giving on the result of student learning. The research population was all students of VII grade in Junior High School 9 Banjarmasin amounting to 306 students with the samples are 32 students of VII F class as the control class and 32 students of VII G class as the experiment class. The methods of data collection through testing and non-testing methods . The type of research is a quantitative research of experimental with pretest-posttest control group design and the methods of analysis are used include validity test, reliability est, preliminary test and t-test to tested the hypothesis. The research found that the population average between the control and experiment class are the same or there is no difference of the population average between the control and experiment class. The conclusion of the research that the effect of reward and punishment giving all together didnât effect significantly on the result of student learning.Â Â